85 Linking Diabetes and Dementia Risk: A Role for Aβ-42 Induced Activation of the NLRP3 Inflammasome? Results from the ENBIND Study. (16th September 2019) - Dyer, Adam; Batten, Isabella; Killane, Isabelle; Woods, Conor; Gibney, James; O'Neill, Desmond; Reilly, Richard; Bourke, Nollaig; Kennelly, Sean
Abstract: Background: Midlife Type 2 Diabetes Mellitus (T2DM) is associated with a greater risk of dementia in later life. The innate immune NLRP3 inflammasome, an innate immune receptor,  has been implicated in both T2DM and Alzheimer's Dementia (AD) and can become activated by Amyloid-β 42 (Aβ-42). We analysed inflammasome-dependent cytokine responses in midlife T2DM and correlated these with cognitive and gait performance Methods: Peripheral Blood Mononuclear Cells (PBMCs) of otherwise healthy patients with T2DM (n=30; 52 ± 8 yrs) and matched controls (n=15; 52.5 ± 7.86 yrs) were incubated for 18h with the following NLRP3 ligands: (i) Lipopolysaccharide (LPS), (ii) Aβ42 or (ii) LPS & Aβ42. Cell supernatants were analysed for production of the inflammasome-dependent cytokine IL-1β. Cognitive function was assessed using the MoCA and gait speed assessed under self-selected, maximal and cognitive dual-task conditions. Mann-Whitney, Wilcoxon tests and linear regression of log-transformed data were used to analyse results Results: Incubation of PBMCs from all participants with NLRP3 agonists was associated with significant production of IL-1β (all p<0.001). There were no statistically significant between-group differences in IL-1β production. MoCA score did not predict IL-1β production by PBMCs. However, poorer performance on the cognitive dual-task gait paradigm was associated with significantly greater IL-1β production in response to LPS & Aβ42 in those with T2DM (p=0.015), which persisted after robust control for demographic, cognitive and cardiovascular covariates (p=0.003). The same association was not seen for healthy controls (p=0.58). Conclusion: Both LPS & Aβ42 induce significant IL-1β production in PBMCs which did not differ between those with midlife T2DM and healthy controls. Poorer performance on the cognitive dual task gait paradigm was associated with significantly greater IL-1β production in response to LPS & Aβ42. Given the value of dual task gait in predicting cognitive decline, longitudinal follow up of this cohort may provide insight into the underlying pathophysiological mechanisms and potential biomarkers of dementia risk in T2DM.